(untitled) (Journal of Atomic and Molecular Sciences, 2021)
In low birefringence fiber, by solving the coupled nonlinear Schrodinger equations contained the Raman effect for satisfy right- and left-handed circularly polarized light in the quasi-CW case, the relationship between the effective polarization beat length and changes of input power have been studied emphatically in low- and high input power situation considering the Raman effect or not. The results showed that the polarization state evolution cycles of the incident light can be changed and meanwhile the transmission distance of the incident light also can be changed due to Raman effect, regardless of the polarization of the incident light was along the slow axis or along the fast axis.